Right adrenal vein: comparison between adaptive statistical iterative reconstruction and model-based iterative reconstruction. Issue 6 (June 2018) - Noda, Y.; Goshima, S.; Nagata, S.; Miyoshi, T.; Kawada, H.; Kawai, N.; Tanahashi, Y.; Matsuo, M.
Abstract : Aim: To compare right adrenal vein (RAV) visualisation and contrast enhancement degree on adrenal venous phase images reconstructed using adaptive statistical iterative reconstruction (ASiR) and model-based iterative reconstruction (MBIR) techniques. Material and methods: This prospective study was approved by the institutional review board, and written informed consent was waived. Fifty-seven consecutive patients who underwent adrenal venous phase imaging were enrolled. The same raw data were reconstructed using ASiR 40% and MBIR. The expert and beginner independently reviewed computed tomography (CT) images. RAV visualisation rates, background noise, and CT attenuation of the RAV, right adrenal gland, inferior vena cava (IVC), hepatic vein, and bilateral renal veins were compared between the two reconstruction techniques. Results: RAV visualisation rates were higher with MBIR than with ASiR (95% versus 88%, p =0.13 in expert and 93% versus 75%, p =0.002 in beginner, respectively). RAV visualisation confidence ratings with MBIR were significantly greater than with ASiR ( p <0.0001, both in the beginner and the expert). The mean background noise was significantly lower with MBIR than with ASiR ( p <0.0001). Mean CT attenuation values of the RAV, right adrenal gland, IVC, and hepatic vein were comparable between the two techniques ( p =0.12–0.91). Mean CT attenuation values of the bilateral renal veins were significantly higher with MBIR than with ASiR ( p =0.0013 and 0.02). Conclusion: Reconstruction of adrenal venous phase images using MBIR significantly reduces background noise, leading to an improvement in the RAV visualisation compared with ASiR. Highlights: MBIR allow a 26.4%–32.7% reduction in background noise. SNR increased by 33.7%–57.4% with MBIR compared with ASiR. MBIR can significantly improve right adrenal vein (RAV) visualization rates.